Enhanced Second Language Vocabulary Learning Through Phonological Specificity Training in Adolescents. Issue 1 (31st October 2018) - van de Ven, Marco; Segers, Eliane; Verhoeven, Ludo
Abstract : This longitudinal randomized trial study investigated the effects of phonological specificity training on second language (L2) vocabulary learning. Eighty‐six Dutch secondary‐school students participated in one of two experimental conditions or in an animacy judgment (active control) condition. Participants in the phonological specificity training (with phonological manipulation) and the picture selection (without phonological manipulation) experimental conditions had to select the corresponding picture from among competitors after hearing a word. Phonological specificity training resulted in increased learning (measured through word translation) compared to the control condition on the posttest whereas picture selection produced increased learning only for participants with larger initial vocabulary sizes. Both experimental conditions showed increased learning for participants with larger vocabulary sizes on the retention test. Compared to picture selection, phonological specificity training showed more learning immediately after intervention for words with nonnative contrasts. Results suggest that phonological features can augment (meaning‐focused) L2 vocabulary learning interventions. Open Practices: This article has been awarded an Open Materials badge. All materials are publicly accessible via the IRIS Repository athttps://www.iris-database.org . Learn more about the Open Practices badges from the Center for Open Science:https://osf.io/vyxz/wiki . Abstract :